Pierre Robin Sequence Posted for Palatoplasty: An Anaesthetic and Analgesia Management - Sonal Sagar Khatavkar; Sravya Bejugama (Journal of Clinical and Diagnostic Research)
Pierre Robin Sequence (PRS) is characterised by micrognathia, glossoptosis, Cleft Palate (CP) and cardiac defects. The key anaesthetic concerns in managing PRS include the patient’s age, assessment of associated congenital birth defects or syndromes and the potential for a shared airway and anticipated difficult intubation. Intubation should be performed using either a nasal or oral endotracheal tube {Ring-Adair-Elwyn (RAE) or flexometallic} of the appropriate size, with video laryngoscopy or fiberoptic equipment available, if necessary. This toddler, a known case of PRS with a CP, with micrognathia since birth and a history of Dandy-Walker syndrome, presented with complaints of feeding difficulties, growth restriction and recurrent Upper Respiratory Tract Infections (URTIs) since birth. The patient was nebulised and premedicated preoperatively. Induction was achieved with sevoflurane and intubation was performed with a flexometallic tube using fiberoptic guidance due to a Cormack-Lehane grade 3, indicating an anticipated difficult airway. Propofol and the muscle relaxant atracurium were administered and a bilateral maxillary block was provided for postoperative analgesia. The case was managed appropriately throughout induction, intraoperatively and during extubation, with an uneventful postoperative recovery.